Pariwisata Era Ekonomi Digital: Sebuah Implementasi Pilar Kebijakan Poros Maritim di Era Jokowi dalam Konteks Paradiplomacy - Laode Muhamad Fathun (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2018)
This paper discusses the role of paradiplomacy in implementing the World Maritime Axis policy in the field of tourism in the digital economy era. With the method of qualitative analysis the writer finds that paradiplomasi plays an active role in the effort to realize the implementation of the World Maritime Axis which is the domain of President Jokowi. Paradiplomasi conducts international cooperation in the form of sister city to promote national tourism which is certainly the leader of the Indonesian sector in the state budget revenues. This then becomes e-diplomacy for local governments and becomes a benchmark in creating e-government and ends in good governance in regional economic development in line with national economy. That is why, hopefully this study is able to become a prescription and become a reference in building an integrated state with the 4.0 era 4.0.